Pharmacogenetic Implementation Lessons From the "Real World". Issue 1 (25th March 2017) - Roden, DM
Abstract : The manuscript "Anticoagulation Endpoints With Clinical Implementation of Warfarin Pharmacogenetic Dosing in a Real‐ World Setting: A Proposal for a New Pharmacogenetic Dosing Approach" describes process outcomes in an institutional program to use pharmacogenetic testing to optimize warfarin dose in a cohort of 257 patients of diverse ancestries. The strengths and weaknesses of the approach and program are discussed, along with the current and potential future status of warfarin as a model for pharmacogenetic testing.